Improved transfection in human mesenchymal stem cells: effective intracellular release of pDNA by magnetic polyplexes. (July 2014) - Delyagina, Evgenya; Schade, Anna; Scharfenberg, Dorothee; Skorska, Anna; Lux, Cornelia; Li, Wenzhong; Steinhoff, Gustav
Aim: Magnetically guided transfection has been shown as a promising approach for the genetic modification of cells. We observed that polyethylenimine (PEI)-condensed pDNA, combined with magnetic nanoparticles (MNPs) via biotin–streptavidin interactions could provide higher transfection efficiency than pDNA/PEI alone, even without the application of a magnetic force. Therefore, we intended to investigate the beneficial properties of MNP-based transfection.Materials & methods: We performed three-color fluorescent labeling of magnetic transfection complexes and traced them inside human mesenchymal stem cells over time using confocal microscopy in order to study pDNA release kinetics by colocalization studies.Results: We demonstrated that MNP-combined pDNA/PEI complexes provide more rapid and efficient release of pDNA than pDNA/PEI alone, which could be explained by the retention of PEI on the surface of the MNPs due to strong biotin–streptavidin interactions.Conclusion: The process of pDNA liberation may significantly influence the efficiency of the transfection vector. Therefore, it should be carefully considered when creating novel gene delivery agents. Original submitted 15 August 2012; Revised submitted 27 February 2013